Media and global conflict: An International Crisis Group case study - Lee Duffield (Asia Pacific Network, 2007)
The Pacific region is part of a larger world, far from being as isolated from centres of global power as a glance at the map might imply, but instead caught up in a web of multilateral relations with binding effects on its future progress and prosperity. This article considers such connections, in regard to both governmental and non-governmental agencies, referring in particular to the proliferation of highly influential non-governmental organisations in the region, as in the world at large. It treats the European Union handling of the December 2006 Fijian coup d'état and its aftermath as a case study in government-to-government relations, and it provides secondly a detailed case study on the operations of one outstanding example of a non-governmental organisation, the International Crisis Group.